(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The world of business is entering a new phase called Industry 5.0. This shift is not only about using advanced technologies or smarter machines. It is also about making industries more human-centered, environmentally responsible, and resilient during times of crisis. In simple terms, Industry 5.0 encourages companies to care not just about profits, but also about people, society, and the planet. However, companies across the world are not adopting sustainability practices in the same way. A business operating in a developed country such as Sweden faces very different conditions compared to a company in an emerging economy like Bangladesh or India, even though both are influenced by the same global sustainability goals. This difference raises an important question: why do some companies strongly integrate sustainability into their operations while others struggle to do so? The study argues that the answer lies in the institutional environment surrounding firms. Every company operates within a system shaped by government regulations, law enforcement, investor expectations, public awareness, and market conditions. These institutional factors strongly influence how seriously businesses adopt sustainability practices. The study focuses on four important elements: the strength of regulations, the effectiveness of enforcement, stakeholder pressure, and the maturity of sustainable markets. Using secondary data and studies published between 2020 and 2025, the paper finds that companies in developed economies are more likely to adopt sustainability because strict laws, active investors, and informed consumers encourage responsible business behavior. In contrast, companies in developing economies often adopt sustainability mainly because international buyers, foreign investors, or export market requirements push them to do so. This unequal pattern of adoption is described in the paper as “institutional asymmetry.” The study also proposes a conceptual model and four research hypotheses that can be tested in future research. Finally, it provides recommendations for policymakers and industry leaders to reduce these institutional gaps and create a more balanced and inclusive approach to sustainability under Industry 5.0.